Love as pedagogy - Loreman, Tim; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
Love is a necessary ingredient of effective pedagogy, yet to this point there has been a distinct lack of serious theoretical and practical work on the topic. What does it really mean to adopt a loving approach to pedagogy? This book provides a pragmatic and thoughtful treatment of the topic of love as pedagogy, examining the use and role of love in teaching and learning, and providing suggestions on how educators can effectively recognise and use love in their work. This text begins with a discussion of what love is, what pedagogy is, and how the two are inseparable in an effective educational context. It then moves on to address ethical considerations. Drawing on discourse on love found in psychology, philosophy, and religion the text examines various aspects of love and their relationship to effective teaching and learning including kindness and empathy, intimacy and bonding, sacrifice and forgiveness, and acceptance and community. This book concludes with a photographic case study of loving pedagogy in action and practical suggestions for educators wishing to adopt the approach. This text is suitable for educators at all levels, especially those in early childhood, elementary, and secondary school settings along with students in education and related programs at universities and colleges. Tim Loreman, PhD., is Professor in the Faculty of Education at Concordia University College of Alberta, Canada. - Publisher's description.
Electronic reproduction.
Keywords: Education -- Study and teaching; Electronic books